Relationship among Job Satisfaction, Organizational Commitment, Employee Loyalty and Employee Retention in the Sri Lankan Banking Industry - Pathirana, Hewa Pathirannahalage Thiwanka Madushani (2023)
Workforce intention to resign is significantly influenced by factors such as job satisfaction and loyalty. Banks in Sri Lanka need to keep their most valuable assets as employees. The purpose of this empirical research is to investigate the relationship between contentment in one's work, dedication to one's organisation, loyalty to one's employer, and job retention in the banking industry in Sri Lanka. Participants come from a wide range of departments and levels within the banking industry. Relationships between variables of interest may be discovered via quantitative data analysis by using statistical methods like correlation analysis as well as regression modelling. Employees who are happy in their jobs are more likely to be dedicated to their companies, according to preliminary research. An engaged workforce is more likely to show loyalty to their employers, and there is a significant correlation between organisational commitment as well as employee loyalty. This study was conducted to determine the elements that influence the workforce's desire to resign among employees of a Sri Lankan banking industry and to examine the relationships between employees' job satisfaction, loyalty decisions, organisational commitment, and resignation intention. 393 randomly chosen banking employees from Sri Lanka were involved in this study. To gather information about the degree of job satisfaction, motivation, and resignation intention, a demographic questionnaire was used. The study's findings showed that all constructs—namely, job satisfaction, motivation, anatomy, and organisational commitment—have a negative link with the intention to leave one's job, which is consistent with other research. Employee loyalty is also investigated as a potential moderator of the connection between organisational commitment as well as employee retention. The preliminary findings point to the importance of employee loyalty as a mediator in the choice of workers to remain with their organisations over the long term. The significance of encouraging work satisfaction and organisational commitment to increase employee loyalty and, hence, improve staff retention rates is highlighted by these results for the Sri Lankan banking sector. Banks may save money on hiring new workers and time and effort spent training current workers if they focus on increasing job satisfaction and fostering a healthy company culture. The study has several caveats, as any other research does, such as the possibility of response bias as well as the fact that it only looks at the banking business in Sri Lanka. Research in the future might broaden its focus to include other sectors and examine a wider range of potential variables that affect staff retention. However, this research adds to the available literature about employee retention in the banking industry of Sri Lanka and provides useful insights for the management of human resources techniques to boost employee engagement as well as loyalty.